Typification of the name Iris benacensis A.Kern. ex Stapf (Iridaceae) - Magrini, Sara; Zucconi, Laura (Phytotaxa, 2020)
The present contribution is related to the project “Italian loci classici census”, promoted by the Italian Botanical Society and aimed at recognizing and typifying all the names of the taxa described from Italy and their loci classici, in order to increase their systematic knowledge and promote further studies (Domina et al. 2012; Brundu et al. 2012; Peruzzi et al. 2019). One of these taxa is Iris benacensis A.Kern. ex Stapf (1887: 649), a species of hybrid origin, often regarded as a heterotypic synonym of I. aphylla Linnaeus (1753: 38) or I. variegata Linnaeus (1753: 38), even if morphologically and genetically distinct (Colasante & Mathew 2008). Iris benacensis was first observed by A. Kerner in northern Italy, near Arco (Trento), and formally described by Stapf (1887). To date, the occurrence of I. benacensis is confirmed only for the Southern Alps, in Trentino Alto Adige near the Lake Garda (known to the Romans as Benacus, from which the name of the species), while the report for Austria needs to be confirmed (Colasante 2014). To the best of our knowledge, the name Iris benacensis was not yet typified.